(untitled) - Rosenberg, Paul (Indianpolis, 2005)
The voluminous 2005 National Electrical Code (NEC)? affects many disciplines, but what you need to know is how it influences your work as an installer. Organized by the type of wiring involved, this indispensable guide extracts and explains only the information that applies to installation. It's a practical reference that highlights what's new, what's changed, and what you must do to comply: * Understand your responsibilities under the 2005 NEC ; * Become familiar with new guidelines for required circuits and load calculations ; * Learn new grounding definitions and requirements for feeder panels ; * Identify the types of conduit and tubing needed for various installations ; * Recognize where guidelines for lighting fixtures have changed ; * Quickly locate code sections relating to HVAC, home appliances, swimming pools, and communication systems ; * See how to bring old installations up to code.
Keywords: Electric wiring,Electric wiring,Commercial buildings,Mạng điện,Mạng điện,Nhà phục vụ kinh doanh; Standards,Insurance requirements,Electric equipment,Installation,Standards,Tiêu chuẩn,Yêu cầu an toàn,Tiêu chuẩn,Trang thiết bị điện